2019
DOI: 10.1155/2019/5730746
|View full text |Cite|
|
Sign up to set email alerts
|

Operational Risk Assessment for International Transport Corridor: A Case Study of China-Pakistan Economic Corridor

Abstract: The international transport corridor is the basis and carrier of economic and trade exchanges between countries and regions. International transport corridors span different countries and regions, coupled with the long distance, complicated transportation environment and process, which determines the potential risks of the operation of the transport corridors. Therefore, accurately identifying and assessing the risk of international channels are an important prerequisite for ensuring its safe and stable operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In this study, infrastructure improvements have been influenced by the introduction of the China-Pakistan Economic Corridor (CPEC), such as the Improvement of Farmers' Quality of Life (QOL) (Kousar, 2018). The results show that the social, cultural and educational interests of local communities are important predictors of the well-being of citizens, and that QOL issues have had a significant impact on the well-being of citizens (Lei et al, 2019). However, the results also showed that community resources have a significant relationship with the thematic wellbeing of the people.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, infrastructure improvements have been influenced by the introduction of the China-Pakistan Economic Corridor (CPEC), such as the Improvement of Farmers' Quality of Life (QOL) (Kousar, 2018). The results show that the social, cultural and educational interests of local communities are important predictors of the well-being of citizens, and that QOL issues have had a significant impact on the well-being of citizens (Lei et al, 2019). However, the results also showed that community resources have a significant relationship with the thematic wellbeing of the people.…”
Section: Methodsmentioning
confidence: 95%
“…Developed economies significantly invest in projects to gather higher returns or attain countless benefits that have essential aspects for boosted economies and people's living standards. Economic relations are mostly dependent on projects that significantly impact on countries (Lei et al, 2019). Therefore, in CPEC, national and economic interests predominate over the definition of various measures.…”
Section: Methodsmentioning
confidence: 99%
“…Boni and Adeney (2020) and Qureshi (2015) additionally revealed that China started to arrange Joint Cooperation Committee (JCC) meetings intermittently on a single platform to resolve various inter-governmental concerns not limited to transparency, decentralization, route, project proposals, security, institutional legalities, and much more through open discussion. Many of the authors including (Boni & Adeney, 2020; Lei et al, 2019; Shah, 2018; Yigit, 2019) in their studies concluded that the political instability and governing weaknesses are the major obstacles against the economic corridor and national domains in Pakistan that may limit economic output to both countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To prove the validity of the model we proposed, we run a case study on railway project accident. Railway project accident is a complex system which may contain transportation accidents, public facility accidents, equipment destruction, environmental pollution, industrial hazard, and economic loss [39]. Furthermore, it is a typical technical accident and is seldom analyzed in emergency research.…”
Section: Introductionmentioning
confidence: 99%